Improving Students Speaking Skill By Using Activities Through Songs at the First Year Students of Class B Semester of English Department Faculty Teachers Training and Pedagogy Lancang Kuning University - Dahler Dahler (Lectura : Jurnal Pendidikan, 2015)
The objective of this research was to find out whether students’ activities throughsong can be used as media for improving the students speaking skill. The participants of thisstudy were the students of semester two B of the English department of Education Facultyand Teachers Training Lancang Kuning University academic year 2009/2010. The number ofsubjects in this research was 21 students. The writer conducted an action research to find theanswer of the problem. In solving the problem, the writer carried out in two cycles, whicheach cycle had four meetings. It was done from April 12th, 2010 until Mei 31st , 2010. Theresearcher and collaborator gathered the data in each meeting in cycle 1 and 2 from thechecklist of observation for teacher and students, field note/recording test and interview.After analyzing the data, it was found that the activities through song improved the students’speaking skill and influenced all indicators of speaking skill in term of accent, grammar,vocabulary, fluency, and comprehension. Furthermore, it built up the students confidence andparticipation in class. The researcher concluded that the students’ activities through song canimprove the students’ speaking skill.